Pelatihan Pemanfaatan Barang Bekas pada Program P5 bagi Bagi Guru dan Siswa Kelas Rendah di SDN IV Sukoharjo - Paradika Angganing; Moefty Mahendra; Pujiyana (Jurnal Masyarakat Indonesia (Jumas), 2024)
The Pancasila student project is carried out by utilizing used goods with the theme of local wisdom. The application of Merdeka curriculum in the project activities to strengthen the students profile of Pancasila (P5) are very important so that teachers and students are more creative and innovative. The solution offered is to provide assistance to teachers and students. The implementation method includes socialization, workshops, and class portfolio exhibitions. The results of this service are that teachers can make teaching modules and P5 criteria, while students can make works from used goods that can be utilized for everyday life. The conclusion of the service that has been carried out is that teachers and students can implement the P5 program well and creatively. Key words: Pancasila student profile, P5, used goods